Ostracoda from the Santonian–Campanian (Upper Cretaceous) Nenjiang and Sifangtai formations, Songliao Basin, northeastern China. (January 2022) - Ye, Yunqi; Xi, Dangpeng; Sun, Lixin; Do Carmo, Dermeval Aparecido; Antonietto, Lucas Silveira; Leite, Amanda Moreira; Qin, Zuohuan; Wan, Xiaoqiao
Abstract: Despite the abundant literature on limnic Cretaceous ostracode faunas, the database on mid-Late Cretaceous taxa is still scarce. The Songliao Basin in northeastern China preserves a diverse assemblage of ostracode fossils from the Santonian–Campanian Nenjiang and Sifangtai formations. This rather unique material is of major importance to comprehend Early to mid-Late Cretaceous (Cenomanian–Campanian) limnic ostracode faunas and therefore the evolution of Late Cretaceous basins in China. A study of this fauna was conducted to detail the taxonomy of ostracode species from members 1 and 2 of the Nenjiang and Sifangtai formations in the Songliao Basin. Well-preserved specimens of 14 ostracode species were recovered from samples of the ZKY2-1 well in southwestern Songliao Basin: Scabriculocypris liaukhenensis Liu in Netchaeva et al., 1959, Ilyocyprimorpha netchaevae Su in Netchaeva et al., 1959, Cypridea acclinia Netchaeva in Netchaeva et al., 1959, Cypridea cavernosa Galeeva, 1955, Cypridea gracile Netchaeva in Netchaeva et al., 1959, Cypridea lepida Ye in DOFEAD, 1976, Cypridea squalida Sou in Netchaeva et al., 1959, Fabaeformiscandona ? Disjuncta (Hao in Hao et al., 1974 ), Lycopterocypris profunda Lübimova, 1956, Mongolocypris magna (Hou, 1958 ), Mongolocypris tera (Su in Netchaeva et al., 1959 ), Talicypridea obliquecostae (Szczechura and Błaszyk, 1970 ), Talicypridea reticulata (Szczechura, 1978 ) and Renicypris renalata (Su in Hao et al., 1974 ). Four of the species identified received emended descriptions and diagnoses. Other important results include the first discussion on sexual dimorphism in Cypridea acclinia and Fabaeformiscandona ? disjuncta, the first study on the ontogeny of Ilyocyprimorpha netchaevae, and the reassignment of Cypridea liaukhenensis to the genus Scabriculocypris . Several species recorded herein are also found in other continental far-eastern Asian basins, while genera range from worldwide to far-eastern Asian distribution; these results support strong affinities among faunas of Mongolia, China, and Japan.